Bakit kinagat ni Adan ang mansanas ni Eva
A story of a probinsyano, Ambo (Dolphy) who falls for a city girl, Evelyn (Beverly Vergel). Ambo courts the girl by doing task like cutting wood for the girl's kin or helping in the laundry. He finally wins her hand in marriage but with some complications. He had promised the girl that he would not do what married couples do for fear of having a baby. the fear is because most of the kin of Evelyn died giving birth. However due to unforseen circumstances the two inevitable consumate their marriage w/c leads to comic situation.
VCD
Dolphy, Beverly Vergel, Panchito, Nova Villa
Keywords: Feature films--Philippines.